INDIVIDUAL RELIGIOUS EXPERIENCE AS A SOURCE OF A RELIGIOUS CONFLICT IN CHRISTIAN TRADITION - R. A. Ivanova (Дискурс)
The problem of sources of intra religious conflicts is considered. The specific character of religious conflicts arising in the Christian church is analyzed. Various manifestations of individual religious experience leading to formation of alternative outlook and, as a result, emergence of the intra religious conflict are revealed.